2013
DOI: 10.1016/j.celrep.2013.07.021
|View full text |Cite
|
Sign up to set email alerts
|

The Calcineurin-NFAT-Angiopoietin-2 Signaling Axis in Lung Endothelium Is Critical for the Establishment of Lung Metastases

Abstract: SUMMARY The pre-metastatic niche is a pre-determined site of metastases, awaiting the influx of tumor cells. However, regulation of the angiogenic switch at these sites has not been examined. Here we demonstrate that the calcineurin-NFAT pathway is activated specifically in lung endothelium prior to the detection of tumor cells that preferentially metastasize to the lung. Upregulation of the calcineurin pathway via deletion of its endogenous inhibitor Dscr-1 leads to a significant increase in lung metastasis d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 30 publications
4
81
0
2
Order By: Relevance
“…In addition, we detected other altered E2F target genes known to function in tumor angiogenesis. Previous studies have demonstrated that Angpt2 can promote angiogenesis (49,50,71) and tumor cell invasion (51,(72)(73)(74). In addition, E2F1 tumors have significantly low levels of Cyr61, and blocking of Cyr61 function decreased metastasis in a xenograft of the MDA-MB231 human breast cancer cell line (52).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we detected other altered E2F target genes known to function in tumor angiogenesis. Previous studies have demonstrated that Angpt2 can promote angiogenesis (49,50,71) and tumor cell invasion (51,(72)(73)(74). In addition, E2F1 tumors have significantly low levels of Cyr61, and blocking of Cyr61 function decreased metastasis in a xenograft of the MDA-MB231 human breast cancer cell line (52).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, treatment with an antibody targeting VEGF receptor 2 (VEGFR2) increased the efficacy of HER2-targeted therapies against established brain metastases from HER2-positive breast cancer in a mouse xenograft model 43 . In animal models, VEGF also exerts pro-metastatic effects through activation of the calcineurin–nuclear factor of activated T cells (NFAT) pathway via upregulation of ANG2 expression in ECs 44 . In line with these preclinical data, high levels of ANG2 expression determined by transcriptomic analysis of tumour samples correlate with an increased metastatic burden in patients with breast cancer 45 .…”
Section: The Abnormal Tumour Vasculaturementioning
confidence: 99%
“…Studies have also been performed examining the microenvironment of the premetastatic site or niche. Loss of DSCR1, an endogenous calcineurin inhibitor, leads to excessive calcineurin/NFAT/angiopoietin-2 (ANG-2) pathway activation in lung endothelium and the establishment of lung metastasis [123]. Increased VEGF level in the lung microenvironment triggers calcineurin/NFAT/ANG-2 signaling activation and promotes angiogenesis in the pre-metastatic niche.…”
Section: Nfats In the Tumor Microenvironmentmentioning
confidence: 99%